Regeneration of the Klothek Lesung of the Sedulur Sikep Community in Blimbing, Sambongrejo Village, Blora Regency - Bernika, Tabita; Aesijah, Siti (Universitas Negeri Semarang, 2025)
Klothek Lesung is a traditional art form of musical entertainment passed down by ancestors from ancient times. It is performed by 4–6 players using pestles (alu) and mortars (lesung) as instruments to produce rhythmic sounds, along with 1–2 singers. This research aims to understand, analyze, and describe the process of musical regeneration of the lesung art form in Blimbing Hamlet, Sambongrejo Village, Sambong District, Blora Regency. The qualitative method emphasizes a socially constructed reality between the researcher and the subjects, resulting in shared social experiences and meaningful insights. An ethnographic approach, one of the approaches in qualitative research, is used by the researcher. The results show that the regeneration process of klothek lesung in Blimbing Hamlet, Sambongrejo Village, Sambong District, Blora Regency, occurs naturally through generations within families, involving their children and grandchildren. The songs taught to accompany the klothek lesung performance include “Lumbung Desa,” “Lesung Jumengglung,” and “Prau Layar.” These three songs are commonly performed to welcome guests visiting Blimbing Hamlet.